Advancements and Clinical Implications of Robotic-Assisted Surgery in Urology: A Decade of Innovation and Outcomes - Patil, Deepak; Patil, Sangameshwar; Mahuli, Kshiti; Devi Patil, Roshini; Rao, Krishna; Abbas, Shaikh Wafa (Journal of Neonatal Surgery, 2025)
Background: Robotic-assisted surgery (RAS) has revolutionized minimally invasive surgery with its enhanced ergonomics, improved magnification, and precise surgical manipulation. Initially validated in procedures like robot-assisted prostatectomy and partial nephrectomy, its application has extended to other complex urological conditions, including bladder cancer and ureteropelvic junction obstruction. Methods: This review synthesizes outcomes from studies comparing robotic-assisted surgeries to both open surgeries and traditional laparoscopic approaches. Emphasis is placed on analyzing morbidity rates, blood loss, hospital stays, and clinical outcomes across various procedures. Additionally, the evolution of surgical technologies and their clinical adoption due to learning curves and cost reductions are examined. Results: Robotic surgeries typically show lower morbidity, reduced blood loss, and shorter hospital stays compared to open surgeries, with comparable clinical outcomes. Despite higher initial costs and setup times, RAS offers a shorter learning curve and reduced operative times compared to traditional laparoscopy. Emerging technologies and market competition are expected to further decrease costs and enhance the accessibility of robotic surgeries. Conclusion: Robot-assisted surgery is likely to replace conventional laparoscopic approaches in many urological procedures. The ongoing development of new platforms and the reduction in costs, coupled with improved surgical training, predict a shift towards more widespread adoption of robotic systems in minimally invasive surgery.